Small saccades versus microsaccades: Experimental distinction and model-based unification. (January 2016) - Sinn, Petra; Engbert, Ralf
Highlights: Small goal-directed saccades differ from microsaccades in a high-acuity task. Both saccade types can be distinguished by their specific couplings to slow drifts. We develop a stochastic-dynamical model of microsaccades and small saccades. Abstract: Natural vision is characterized by alternating sequences of rapid gaze shifts (saccades) and fixations. During fixations, microsaccades and slower drift movements occur spontaneously, so that the eye is never motionless. Theoretical models of fixational eye movements predict that microsaccades are dynamically coupled to slower drift movements generated immediately before microsaccades, which might be used as a criterion to distinguish microsaccades from small voluntary saccades. Here we investigate a sequential scanning task, where participants generate goal-directed saccades and microsaccades with overlapping amplitude distributions. We show that properties of microsaccades are correlated with precursory drift motion, while amplitudes of goal-directed saccades do not dependent on previous drift epochs. We develop and test a mathematical model that integrates goal-directed and fixational eye movements, including microsaccades. Using model simulations, we reproduce the experimental finding of correlations within fixational eye movement components (i.e., between physiological drift and microsaccades) but not between goal-directed saccades and fixational drift motion. These results lend support to a functional difference between microsaccades and goal-directed saccades, while, at the same time, both types of behavior may be part of an oculomotor continuum that is quantitatively described by our mathematical model.